KONTRIBUSI PENDAPATAN SOPI TERHADAP PENDAPATAN MASYARAKAT DI NEGERI EMA, KOTA AMBON - Catriona Triselia Rahayaan; Evelin Parera; Wilma Imlabla (MARSEGU : Jurnal Sains dan Teknologi, 2025)
This study aims to analyze the contribution of sopi's business income to the household income of sopi farmers and compare it with the income of non-sopi farmers in Ema, Ambon City. The study used a descriptive quantitative approach with Systematic Random Sampling of 30 respondents from 60 sopi farmer populations and an additional 30 respondents from non-sopi farmer community groups. The results showed that sopi business contributed 69.92% to the household income of farmers or an average of Rp. 1,542,500 per household per month, while non-sopi income accounted for 30.08%. Meanwhile, sopi's non-farmer community has a more diverse source of income with a predominance of the formal and service sectors, contributing 57% to the total community income. Factors that affect sopi's production and sales include weather conditions, fuel availability, and sopi's illegal legal status.